PENGARUH KUALITAS LAYANAN PERUSAHAAN PENERBANGAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA PELANGGAN MASKAPAI LION AIR DI KOTA BANDA ACEH - Iin Karnita, Nurdasila (Departemen Manajemen, 2018)
This research aimed to measure the effect of service quality pre-flight and service quality inflight to customer loyality of customer’s Lion Air Airlines in Banda Aceh with customer satisfaction as mediating variabel. The sample used in this research are customer’s Lion Air Airlines in Banda Aceh which totaled 99 respondents. The instrument of collecting data in this research is questionnaire. uses non-probability purposive sampling technique was used as sampling technique. As much of 100 questionnaires distributed and only just 99 questionnaires could be collected. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all variables involved in this research. The results are follows: 1) service quality pre-flight significantly effect to customer loyality of customer’s Lion Air Airlines in Banda Aceh. 2) service quality in-flight significantly effect to customer loyality of customer’s Lion Air Airlines in Banda Aceh. 3) service quality pre-flight significantly effect to customer satisfaction of customer’s Lion Air Airlines in Banda Aceh . 4) service quality in-flight significantly effect to customer satisfaction of customer’s Lion Air Airlines in Banda Aceh. 5) customer satisfaction significantly effect to customer loyality of customer’s Lion Air Airlines in Banda Aceh. 6) customers satisfaction mediate the effect of service quality pre-flight to customer loyality of customer’s Lion Air Airlines in Banda Aceh., And 7) customers satisfaction mediates the effect of service quality n-flight to to customer loyality of customer’s Lion Air Airlines in Banda Aceh.